Effectiveness of Conceptual Understanding Procedures (CUPs) Learning Model on Students' Understanding of Physics Concepts - Nadia, Zalwa; Sapiruddin, Sapiruddin; Zahara, Laxmi; Juandi, Tarpin; Wajdi, Badrul (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This study aims to determine the effectiveness of the Conceptual Understanding Procedures (CUPs) learning model on students' understanding of physics concepts at MA Muallimat NWDI Pancor. The type of research used is truly experimental with a posttest only control design. The population of the study was all students of class XI MIPA at MA Muallimat NWDI Pancor. The sampling technique used was simple random sampling. The selected samples were class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. The data collection technique used a concept understanding test. The posttest results show that the conceptual understanding of students in the experimental class using the Conceptual Understanding Procedures (CUPs) learning model is higher than that of the control class taught using the conventional learning model. Based on the results of the data analysis, the hypothesis test calculation using the right-hand t-test formula at a significance level of 5% gives tcount = 2.388 and ttable = 1.669. From these results, it can be seen that the tcount value > t_table (2.388 > 1.669), so Ho is rejected and Ha is accepted. The effect size is 0.56, which is included in the medium category. This shows that the application of the Conceptual Understanding Procedures (CUPs) learning model is effective for students' understanding of physics concepts at MA Muallimat NWDI Pancor on the topic of optics.